(untitled) (Journal of Parents and Teachers, 2026)
When the time comes to decide which degree course to study, it can also bring with it a fear of making the wrong choice, confusion and even anxiety, as Susana shares on this page. The first step is to maintain your inner peace and freedom. Rather than worrying about getting it right or avoiding mistakes, it’s about making a good decision – a process that takes time, as you gradually gather more information. Perhaps it would be good to focus on the profession you want to pursue rather than the degree course itself. The degree course should be chosen based on the profession, not the other way round. From there, you can consider some of the factors suggested here: are you looking to fulfil what you consider your personal calling? Do you want a profession that offers you independence, allows you to travel, or involves helping those most in need.